Motivating patients to exercise. Issue 2 (February 2015) - Li, Chu-Shiu; Liu, Chwen-Chi; Tsai, Min-Kuang; Tai, Ya-Ping; Wai, Jackson Pui Man; Tsao, Chwen-Keng; Wen, Chi-Pang
<x xml:space="preserve">Abstract</x> Objective: Even with the 2008 physical activity guidelines for Americans and the strong epidemiological evidence, physicians are not routinely emphasizing the importance of exercise. We try to explore an innovative way to communicate the benefits of physical activity in a term familiar to patients. Methods and results: A cohort of 470 163 adults from a medical screening program in Taiwan were recruited between 1994 and 2008. Their vital status was followed up by matching with the National Death File. Individuals were classified as 'inactive', 'low active', or 'fully active', with 'fully active' meeting the current exercise recommendation of 150 min per week or more. Cox proportional model was used to calculate the hazard ratio. More than one-half of the cohort was inactive (54%), with one-quarter fully active (24%). One in seven was hypertensive (14%), defined as SBP at least 140 mmHg. Among the hypertensive individuals, mortality risks were increased by 37% for the inactive. Inactive individuals had higher all-cause mortality than active ones across all blood pressure (BP) levels. At 110–119 mmHg, the inactive had a risk as high as the risk at 155 mmHg, an increased mortality risk equivalent to a risk of BP increase of 41.2 mmHg. Conclusion: The mortality risk of being inactive was equivalent to an increase of around 40 mmHg in SBP or 20 mmHg in DBP, a number relevant to hypertensive patients. Appreciating this relationship may convince the inactive to start exercising, a behavior as important as controlling BP.